ANALYSIS OF FACTORS THAT AFFECT DELAYED DEVELOPMENT IN CHILDREN AGE 12-24 MONTHS IN YOGYAKARTA HOSPITAL - lailatuz laila zaidah (Universitas Widya Husada Semarang, 2020)
ABSTRACT Children are the nation's next generation, so the quality of future generations depends on the quality of children's development, especially in infants aged three years (toddlers), because the first three years of life, growth and development of brain cells are still ongoing. It is said to be a golden period because infancy lasts very briefly and cannot be repeated again. It is said to be a critical period because at this time the baby is very sensitive to the environment and requires good nutrition and stimulation for growth. and its development. Between growth and development must run simultaneously. While delayed development is a developmental disorder which is usually caused by risk factors of pre-natal, natal, and post-natal. This study will identify the relationship between the behavior of providing developmental stimulation to improve children's motor development in overcoming delayed development in children aged 12-24 months, by examining using the DDST II Test (Denver Development Screening Test) II. Methods This study uses an analytic observational design with a cross sectional approach, with a multivariate analysis design. The sampling method uses purposive sampling technique with the number of research respondents as many as 60 children in the Yogyakarta PKU Hospital and the independent clinic Child Growth. The results of the nonparametric statistical analysis test with the Likelihood Ratio in gross motor development obtained significance values α = 0.01; whereas in the development of fine motor, a significance value of α = 0.01 is obtained, while in the development of language, a significance value of α = 0.00 The conclusion of this study is the relationship between the behavior of stimulation with the development of gross motor, fine motor, and language. The specific objective is to find out the behavior of development stimulation in overcoming delayed development in children aged 12-24 months Keyword: development, delayed development, developmental stimulation